2005
DOI: 10.1200/jco.2005.02.9876
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Utility of Circulating Methylated DNA in Serum of Melanoma Patients Receiving Biochemotherapy

Abstract: Detection of circulating methylated DNA in serum can predict response to BC and disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
138
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(146 citation statements)
references
References 42 publications
5
138
1
2
Order By: Relevance
“…In patients with malignancies, aberrant methylation of serum DNA has been reported (Müller et al, 2003;Ibanez de Caceres et al, 2004;Fiegl et al, 2005;Mori et al, 2005;Koyanagi et al, 2006). We have detected cell-free tumour DNA in serum of neuroblastoma patients (Gotoh et al, 2005).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In patients with malignancies, aberrant methylation of serum DNA has been reported (Müller et al, 2003;Ibanez de Caceres et al, 2004;Fiegl et al, 2005;Mori et al, 2005;Koyanagi et al, 2006). We have detected cell-free tumour DNA in serum of neuroblastoma patients (Gotoh et al, 2005).…”
Section: Discussionmentioning
confidence: 51%
“…The presence of tumour-derived DNA within the blood stream has been identified earlier (Müller et al, 2003;Fiegl et al, 2005;Mori et al, 2005). Recently, one study showed that the detection of circulating tumour cells was correlated with tumour-related methylated DNA in patients with melanoma (Koyanagi et al, 2006), suggesting that circulating tumour cells are a potential source of circulating methylated DNA.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…16 Circulating cell free tumor DNA has been detected in plasma and serum by assessing allelic imbalance at microsatellite markers [17][18][19] and tumor-related gene methylation. [20][21][22] Recent studies indicate that these markers may show a predictive value of the response to biochemotherapy in stage IV patients. 23,24 Here, we report the results of a pilot study aimed at evaluating the BRAFV600E mutation as a molecular marker in circulating DNA from cutaneous melanoma patients.…”
mentioning
confidence: 99%
“…For example, detection of methylated DNA from the MYOD1 CpG island is associated with reduced disease-free and overall survival in cervical cancer . Similarly, detection of circulating methylated DNA in the serum of patients with melanoma has prognostic value (Mori et al, 2005). The other area in which epigenetics has great clinical potential is in the early detection of cancer relapse in routine patient followup.…”
Section: Epigenomic Profiles As Markers Of Tumour Prognosismentioning
confidence: 99%